The personnel training’s innovative technologies for the social protection of the population - Olga A. Anikeeva, Svetlana N. Kozlovskaya, Valeriya V. Sizikova, (Opción, 2019)
The aim of the study is to investigate the innovative technologies of the personnel training for the social protection of the population. The methods of applied modelling, social and educational experiments are preferred among other applied methods. The discussions in the relevant literature concern the issue of the status of social work as a profession. The analysis of the relevant literature and our own research allowed us to make the following conclusion: all these contradictions can be solved through the innovative teaching technologies that include active and interactive methods, game-based technologies, competitive and interactive methods in education, student Olympics.